9. Specific Aspects of School Competency Assessment in Plastic Education Classes - Brițchi Aliona (Sciendo, 2023)
The article defines evaluation as a strategy for the development of school competencies in plastic education classes. Reveals the advantages of the criterion assessment through descriptors of the educational products, carried out based on the evaluation objectives through traditional and complementary evaluation samples.